Dubai Police effectiveness in combating rumours through social media - AlHajeri, Alya Saleh Ahmed Abdala (2024)
Media plays a crucial role in modern society by enabling communication and sharing importance information with the public. However, there have been instances of social media platform in Dubai being responsible for spreading rumours and false news, leading to public outrage and confusion. This study aimed to assess the effectiveness of Dubai Police’s crisis management in combating rumours and false information. This research investigated the causes of these issues and evaluated the various strategies implemented by the UAE government to regulate and control the dissemination of false information. This study used a mixed-method approach, including survey of 337 Dubai Police officers from various ranks and semi-structured interviews with 4 key informants. The data was comprehensively analyzed using IBM SPSS Amos and MAXQDA software. The findings indicated that Dubai Police officers recognized the significant role of social media in disseminating information as well as the potential risks of spreading rumours and false information. Further, it revealed that Dubai Police officer had adequate knowledge in addressing this issue and emphasize on educating the public about the negative impacts of spreading rumours and false information on social media. The study also revealed that Dubai Police officers took proactive measures to prevent the spread of rumours and false information by collaborating with social media platforms to implement algorithms that prioritize information, partnering with fact-checking organizations, and taking legal action against individuals who were involved with spreading falsehoods. This research concluded that the Dubai Police officers successfully prevented the spread of rumors and false information on social media platforms. Their active monitoring, investigation, and legal interventions, combined with efforts to raise public awareness, have helped maintain social media platforms as safe and reliable sources of information for the public